ANTIOXIDANT ACTIVITY OF PURSLANE PLANT (Portulaca oleracea L.) EXTRACT AS AN ANTIAGING SERUM IN SPRAY GEL USING DPPH METHOD - Desy Ayu Irma Permatasari; Tatiana Siska Wardani; Ikrima Rahmasari; Kezia Putri Maha Dewi (Universitas Muhammadiyah Magelang, 2021)
Skin aging is a problem for women caused by external factors, namely exposure to free radicals such as sunlight, antiaging cosmetic products containing antioxidants have been widely circulated to maintain skin health from the effects of free radicals. The content of antioxidant chemical compounds in the purslane plant (Portulaca oleracea L.) is believed to be able to prevent free radicals. Purslane plant extract serum preparations were made by formulating preparations with ingredients such as HPMC, chitosan, tween 80. Furthermore, antioxidant testing of extracts and preparations of serum spray formulas was carried out using the DPPH method, after which evaluation of the preparations included homogeneity, pH, adhesion, viscosity, and hedonic. The preparation of purslane plant extract serum in the spray gel preparation produces a brownish green color, has a slightly sour smell and has a soft texture. The resulting viscosity in the serum ranged from 1330 - 1362 cPs with a pH value in the range of 5.67 - 5.72. From the hedonic test carried out, the results obtained were that the color and aroma were less favored by the panelists while for the convenience of using spray gel the panelists liked the texture of all purslane (Portulaca oleracea L.) plant extract formulas. Based on this research, the IC50 value of purslane (Portulaca oleracea L.) plant extract was 132.87 ppm, while the formula had an IC50 value of 83.91 ppm. Therefore, antiaging serum in spray gel formulation has stronger antioxidant activity than purslane (Portulaca oleracea L.) plant extract.